Total Quality Management and Six Sigma 2012
DOI: 10.5772/46106
|View full text |Cite
|
Sign up to set email alerts
|

Some Applicable Methods to Analyze and Optimize System Processes in Quality Management

Abstract: Additional information is available at the end of the chapter http://dx.doi.org/10.5772/46106Total Quality Management and Six Sigma 132 amount of investments adequate to achieved quality and safety levels that may be guaranteed for the allocated money), to users (the forecast made in time has mobilized them on the basis of the 'forewarned is forearmed' concept; using our recommendations, in utilization stage they can extract from the system the best effects, that were assumed in concept, design&development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 6 publications
1
51
0
4
Order By: Relevance
“…The probabilistic model "Protection against dangerous influences", developed of authors of this work, and ideas for new models generations [1][2][3][4][5][6] are chosen. It allows to estimate CHSS reliability for technology 1 (proactive diagnostic of system integrity) and more general technology 2 (monitoring).…”
Section: The Analysis Of Specificity and Choice Of Probabilistic Modementioning
confidence: 99%
“…The probabilistic model "Protection against dangerous influences", developed of authors of this work, and ideas for new models generations [1][2][3][4][5][6] are chosen. It allows to estimate CHSS reliability for technology 1 (proactive diagnostic of system integrity) and more general technology 2 (monitoring).…”
Section: The Analysis Of Specificity and Choice Of Probabilistic Modementioning
confidence: 99%
“…For estimations of these metrics (Т full.i and Т full.i2 ) with reference to Technologies 1, 2, and 3 it is purposed to use classical models of the queueing theory [1][2]4]. For Technologies 4 and 5, the formulas received earlier in works [3,[5][6][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] are applicable. Thus, frequencies of arriving calls (λ i ) and the average time of performing calls of i-th type (β i1 ) form an input for modelling.…”
Section: Formalization For Estimation Of Possible Delaysmentioning
confidence: 99%
“…For modelling and estimations, software tools complexes CEISOQ [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Results of the analysis have shown that at the expense of the choice of rational dispatcher Technology 5 and its optimizing parameters the relative portion of well-timed performed calls is 3 times greater in comparison with the today applied Technologies 1 and 4. And the value of damages can be really reduced!…”
Section: Example Of Rational Dispatchingmentioning
confidence: 99%
See 2 more Smart Citations